Serum BDNF increase and the role of cortisol reduction following contemplative mental training. (September 2021) - Puhlmann, L.; Vrtička, P.; Linz, R.; Papassotiriou, I.; Chrousos, G.P.; Engert, V.; Singer, T.
Abstract : Chronic stress exposure reduces expression of brain derived neurotrophic factor (BDNF) in animal and disease models. The stress-hormone cortisol has an antagonistic relationship with BDNF and may be implicated in this process. Previous work including our own suggests that contemplative mental training interventions like mindfulness-based stress reduction can effectively reduce acute and long-term cortisol exposure. As part of the ReSource Project, we investigated whether a nine months long contemplative mental training intervention increases serum BDNF levels. 332 healthy adults were randomly assigned to either a control or an intervention group. Training consisted of three distinct 3-month long modules focusing on 1) attention and interoception, 2) socio-affective skills or 3) socio-cognitive skills. Linear mixed model analyses revealed a significant time-by-training-condition interaction (Chi2(7) = 28.2, p <.001, ω2 = 0.04). BDNF levels in the control cohort followed an unstable pattern. In the training cohorts, BDNF levels increased over the first three months of attention and interoception-based training. At six and nine months of training, they stabilized or continued to increase depending on the cohort. Mediation analyses revealed a small indirect effect of training on BDNF via lowered cortisol levels in hair. Associations with further stress-related indices were explored. Mental training may enhance peripheral BDNF levels in part by reducing participants' stress load.